2001
DOI: 10.1034/j.1600-0714.2001.300104.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal lesions and risk habits among men in an Italian study population

Abstract: A randomly selected study population of 118 male subjects (> or = 40 years) living on the Mediterranean island of Pantelleria (southwest of Sicily, Italy) was examined for the presence of oral mucosal lesions, with particular emphasis on the early diagnosis of oral precancerous and cancerous lesions. The study population was interviewed for socioeconomic and behavioural information, and clinically examined using WHO criteria. The prevalence of oral mucosal lesions observed, and data obtained about oral hygiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
89
8
23

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 23 publications
19
89
8
23
Order By: Relevance
“…14,15,22,24,25, Although overt cancers were recorded, the most common relevant lesion was 'leukoplakia' and therefore most of these studies may be regarded as demonstrating the prevalence of this entity. However leukoplakia is poorly defined and, similar to the current study, most can be regarded as recording mainly the prevalence of persistent white or keratotic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,22,24,25, Although overt cancers were recorded, the most common relevant lesion was 'leukoplakia' and therefore most of these studies may be regarded as demonstrating the prevalence of this entity. However leukoplakia is poorly defined and, similar to the current study, most can be regarded as recording mainly the prevalence of persistent white or keratotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However this included pigmentation (24.6%) and 'linea alba' (10.7%). In another study of a random sample of Sicilian men mucosal lesions were found in 81% of the group, 24 but this included over 50% with 'coated tongue' . Nevertheless the prevalence of leukoplakia in this group was 13.8%, which was ascribed to the high numbers who used alcohol and tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In Sri Lanka, the prevalence of oral leukoplakia has been reported as 26.2 per 1000, respectively 29 and in Italy, 16 (13.6%) among 118 randomly selected male population. 30 A Swedish study indicated 0.1% of 15-24 year old persons had idiopathic leukoplakia and 0.8% had tobacco-associated leukoplakia. 31 Prevalence of leukoplakia and mucosal disease in regular smokeless tobacco users ranged from 8 to 43%.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] The Vale do Jequitinhonha is a region largely known for its low social indicators and is currently one of the areas of greatest inequality and social exclusion in Brazil. 15 The microregion of Diamantina is located in this region and is known as the gateway to the Vale do Jequitinhonha.…”
Section: Introductionmentioning
confidence: 99%